(untitled) (Journal of Atomic and Molecular Sciences, 2014)
We propose a news cheme to prepare the Greenberger-Horne-Zeilinger states and atomic Schrödinger cat states for N trapped ions. This scheme is based on the interaction of N trapped ions with a frequency-modulated traveling wave light field. Preparations of these states can be all complished by one-step operation.